Biological Alternative Conceptions of Secondary School Students About Heredity: A Case Study - Farkhanda Iqbal; Muzammila Akram (Research Journal of Psychology, 2024)
Primarily the study is intended to diagnose Alternative conceptions of secondary level student about heredity to comprehend the main ideas of the heredity like cell cycle, mitosis, meiosis. Like vise it also explored the main reasons that develop alternative conceptions. To attain the objectives of the study case study was acquired. Four (4) public schools of Bahawalpur city were selected through random sampling. Formerly 200 students of IX grade were selected as a purposive sample of the research work. A distinct instrument labelled as a diagnostic test to quantify the alternative conceptions about heredity (DT). Renowned and experienced subject specialists of biology authenticated the (DT). To find the reliability a pilot test was intended through test retest method. The coefficient relation (r) was (0.96). To measure the internal consistency of the instrument. the Cronbach alpha coefficient was calculated through SPSS 2026 version; its value was (0.87). On the base of result of diagnostic test interview 50 students were selected purposively. The result indicated that 20% items were concept based. So prior weak knowledge, second language difficulty, poor explanation of lecture created alternative conception. On the base of findings recommendations were proposed e.g. (active participation of learning, use of teaching aids) for better understanding.